A moderated mediation model for explaining residents’ environmental and cultural responsible behavior - Jiang, Xiufang; Gossage, Mollie G. (Frontiers in Psychology, 2025)
IntroductionThe sustainable development of tourism in ethnic minority regions critically hinges on local residents’ adoption of environmentally and culturally responsible behaviors, yet the mechanisms and boundary conditions of the interplay among these core elements are unclear.MethodsThis empirical study integrates the theory of planned behavior (TPB), social capital theory (SCT), place attachment theory (PAT), and relative deprivation theory (RDT) to investigate factors influencing environmentally and culturally responsible behavior (RB) among residents in western Sichuan, China. Data were collected via an online survey of residents.ResultsSurvey data reveal that environmental and cultural attitudes (ECA), government trust (GT), and place attachment (PA) directly promote RB, with perceived tourism impact (PTI) mediating these relationships. Additionally, relative deprivation (RD) moderates the influence of GT and PA on RB, as well as the mediating effect of PTI on the pathways from ECA and PA to RB.DiscussionThis study contributes to the existing literature on tourism sustainability and destination resident behavior by illustrating that improving local responsibility requires strengthening cultural attitudes in addition to environmental attitudes, building local trust in the government, and fostering place attachment. Furthermore, the effectiveness of these goals depends on mitigating communities’ relative deprivation. These findings are significant for both theory and practice, and the conclusion contains policy insights and practical strategies for the sustainable development of ethnic minority area tourism communities.